Natural Dietary Supplement, Carvacrol, Alleviates LPS-Induced Oxidative Stress, Neurodegeneration, and Depressive-Like Behaviors via the Nrf2/HO-1 Pathway - Naeem K (Dove Medical Press, 2021)
Komal Naeem,1,2,* Lina Tariq Al Kury,3 Faiza Nasar,1,* Abdullah Alattar,4 Reem Alshaman,4 Fawad Ali Shah,1 Arif-ullah Khan,1 Shupeng Li2 1Department of Pharmacology, Faculty of Pharmaceutical Sciences, Riphah International University, Islamabad, 747424, Pakistan; 2State Key Laboratory of Oncogenomics, School of Chemical Biology and Biotechnology, Shenzhen Graduate School, Peking University, Shenzhen, 518000, People’s Republic of China; 3College of Natural and Health Sciences, Zayed University, Abu Dhabi, 49153, United Arab Emirates; 4Department of Pharmacology and Toxicology, Faculty of Pharmacy, University of Tabuk, Tabuk, 71421, Saudi Arabia*These authors contributed equally to this workCorrespondence: Fawad Ali ShahDepartment of Pharmacology, Faculty of Pharmaceutical Sciences, Riphah International University, 7th Avenue, Sector G-7/4, Islamabad, 747424, PakistanTel +92-51-2891835-38Fax +92-51-2891471Email fawad.shah@riphah.edu.pkShupeng LiState Key Laboratory of Oncogenomics, School of Chemical Biology and Biotechnology, Shenzhen Graduate School, Peking University, Shenzhen, 518000, People’s Republic of ChinaEmail lisp@pku.edu.cnPurpose: Major depressive disorder (MDD) is a debilitating human health condition characterized by mood swings and is associated with a high probability of suicide attempts. Several studies have reported a role of neuroinflammation in MMD, yet the efficacy of natural drug substances on neuroinflammation-associated depression has not been well-investigated. The present study examined the neuroprotective effects of carvacrol on lipopolysaccharide (LPS)-induced neuroinflammation, depression, and anxiety-like behavior.Methods: Male Sprague Dawley rats were divided into two experimental cohorts to determine the effects and the effective dose of carvacrol (whether 20 mg/kg or 50 mg/kg), and further demonstrate the mechanism of action of nuclear factor E2-related factor (Nrf2) in depression.Results: We found marked neuronal alterations in the cortex and hippocampus of LPS-intoxicated animals that were associated with higher inflammatory cytokine expression such as cyclooxygenase (COX2), tumor necrosis factor-alpha (TNF-α), and c-Jun N-terminal kinase (p-JNK). These detrimental effects exacerbated oxidative stress, as documented by a compromised antioxidant system due to high lipid peroxidase (LPO). Carvacrol (20 mg/kg) significantly reverted these changes by positively modulating the antioxidant gene Nrf2, a master regulator of the downstream antioxidant pathway. To further investigate the role of Nrf2, an inhibitor of Nrf2 called all-trans retinoic acid (ATRA) was used, which further exacerbated LPS toxicity with a higher oxidative and inflammatory cytokine level. To further support our notion, we performed virtual docking of carvacrol with the Nrf2-Keap1 target and the resultant drug-protein interactions validated the in vivo findings.Conclusion: Collectively, our findings suggest that carvacrol (20 mg/kg) could activate the endogenous master antioxidant Nrf2, which further regulates the expression of downstream antioxidants, eventually ameliorating LPS-induced neuroinflammation and neurodegeneration.Keywords: depression, neuroinflammation, Nrf2 pathway, lipopolysaccharide, carvacrol, neurodegeneration